A development of e-Muslim personalization system / Norahmah Ismail - Ismail, Norahmah (2005)
E-Muslim Personalization System is a web-based system that allows users to keep and update their personal Muslim duty such as zakah, Islamic inheritance (faraid) and wills (wasiat). The system is not only calculates zakah and faraid but it also ability to calculate the user's assets, debts and save them in separate files. E-Muslim Personalization System is based on the problems faced by Muslims in way to know their obligation in religion. People in Malaysia still lack of knowledge about faraid, zakah and wasiat. No wonder we have heard that some families are split oust because of estate of a deceased person. Besides, we are still not clear about certain things in zakah such as who are supposed to pay zakah , what type of zakah indeed has to be paid, how much zakah is supposed to be paid. In order to ensure the objective is achieve. System Development Life Cycle (SDLC) approach is used to guide the system development process. The calculation of zakah and faraid are based on Quran, Hadith and rules of Shafie. The range or amount from this calculation might not be the exact amount required by the Syariah court and Baitulamal but it can be a guideline or reference for user.